The role of perceived risks on mobile payment adoption: Evidence from Asia - Benson, V. (2023)
Mobile has become an expected method of payment irrespective of the geographical location or the level of technology adoption across the developed and developing countries. The differences of adoption rates between China and Japan are significant, warranting further research into the barriers to mobile payment. To fill this research gap, we propose and empirically test a theoretical model of mobile payment adoption by users in China, Taiwan, and Japan. A decision-tree method was used to analyse 726 questionnaire responses. The results reveal that innovators, early adopters, and the early majority categories are concerned about the performance risk of mobile payment adoption and innovators, early adopters, and the late majority categories are concerned about the security risk of mobile payment adoption. The findings will help 5G mobile services vendors develop consumer trust and increase the contributions of the mobile industry to GDP.